Sense of coherence, sociodemographic, lifestyle, and health-related factors in older adults' subjective well-being - von Humboldt, Sofia (2015)
Objectives: This research explores a structural model of predictors of subjective well-being (SWB) in a community-dwelling older population. Methods: A community sample of 1258 older adults was assessed regarding SWB, sense of coherence and sociodemographic, lifestyle, and health-related characteristics. Structural equation modeling was used to investigate a structural model of the self-reported SWB, comprising sense of coherence, sociodemographic characteristics (age, sex, marital status, household, professional status, educational level, social support, living setting, and self-reported spirituality), as well as lifestyle and health-related characteristics (leisure, physical activity, recent disease, perceived health, and medication). Results: Self-reported spirituality (b ¼ 0.395; p < 0.001), sense of coherence (b ¼ 0.128; p < 0.001), social support (b ¼ 0.089; p ¼ 0.008), living setting (b ¼ 0.083; p < 0.001), household (b ¼ 0.072; p < 0.001), perceived health (b ¼ 0.049; p ¼ 0.007) and medication (b ¼ 0.015; p ¼ 0.033) predicted SWB. The variables accounted for 82.9% of the variability of SWB. Conclusion: Self-reported spirituality is the strongest predictor of SWB. Other predictors are sense of coherence, social support, living setting, household, perceived health, and medication. Results emphasize that health care approaches may benefit from clearly understanding SWB and its predictors, as essential for promoting older adults' health and well-being.